A Critical Exploration of Women's Gendered Experiences in Outdoor Leadership. (March 2019) - Rogers, Elizabeth Bond; Rose, Jeff
Background: Although outdoor education provides many positive learning outcomes for students, it is a field in which women continue to be underrepresented in leadership roles. Centering the voices of women and other underrepresented populations is critical to creating a more inclusive outdoor education field.Purpose: The purpose of this study was to explore women's experiences as outdoor leaders, and how women's perspectives may broaden how outdoor leadership is defined and conceptualized.Methodology/Approach: The study was grounded in narrative inquiry and a critical feminist framework and included interviews and photo reflections of six participants identifying as women outdoor leaders in higher education.Findings/Conclusions: Participants experienced sexism, gender bias, and lack of confidence in technical skills as outdoor leaders. Participants discussed how they conceptualize outdoor leadership through a lens of facilitation and discovery, challenging masculine norms and ideologies. In addition, participants' intersections of identities influence how they experience outdoor leadership.Implications: Implications from this study indicate the continued need to center the voices of women and diverse populations, using critical frameworks nascent in outdoor education studies. In addition, critical examinations of policies and practices that may reify the White male privileged narrative of outdoor education are needed.